Effect of a High Fat Diet vs. High Carbohydrate Diets With Different Glycemic Indices on Metabolic Parameters in Male Endurance Athletes: A Pilot Trial - Zdzieblik, Denise; Friesenborg, Hilke; Gollhofer, Albert; König, Daniel (Frontiers in Nutrition, 2022)
Consuming low glycemic carbohydrates leads to an increased muscle fat utilization and preservation of intramuscular glycogen, which is associated with improved flexibility to metabolize either carbohydrates or fats during endurance exercise. The purpose of this trial was to investigate the effect of a 4-week high fat low carbohydrate (HFLC-G: ≥ 65 % high glycemic carbohydrates per day; n = 9) vs. high carbohydrate low glycemic (LGI-G: ≥ 65 % low glycemic carbohydrates daily; n = 10) or high glycemic (HGI-G: ≥ 65 % fat, ≤ 50 g carbohydrates daily; n = 9) diet on fat and carbohydrate metabolism at rest and during exercise in 28 male athletes. Changes in metabolic parameters under resting conditions and during cycle ergometry (submaximal and with incremental workload) from pre- to post-intervention were determined by lactate diagnostic and measurements of the respiratory exchange ratio (RER). Additionally, body composition and perceptual responses to the diets (visual analogue scale [VAS]) were measured. A significance level of α = 0.05 was considered. HFLC-G was associated with markedly decreased lactate concentrations during the submaximal (−0.553 ± 0.783 mmol/l, p = 0.067) and incremental cycle test (−5.00 ± 5.71 [mmol/l] x min; p = 0.030) as well as reduced RER values at rest (−0.058 ± 0.108; p = 0.146); during the submaximal (−0.078 ± 0.046; p = 0.001) and incremental cycle test (−1.64 ± 0.700 RER x minutes; p < 0.001). In the HFLC-G fat mass (p < 0.001) decreased. In LGI-G lactate concentrations decreased in the incremental cycle test (−6.56 ± 6.65 [mmol/l] x min; p = 0.012). In the LGI-G fat mass (p < 0.01) decreased and VAS values decreased indicating improved levels of gastrointestinal conditions and perception of effort during training. Main findings in the HGI-G were increased RER (0.047 ± 0.076; p = 0.117) and lactate concentrations (0.170 ± 0.206 mmol/l, p = 0.038) at rest. Although the impact on fat oxidation in the LGI-G was not as pronounced as following the HFLC diet, the adaptations in the LGI-G were consistent with an improved metabolic flexibility and additional benefits regarding exercise performance in male athletes.